2017
DOI: 10.18203/2320-6012.ijrms20170139
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and clinical profile of diabetic foot ulcer using optimal culture techniques

Abstract: INTRODUCTIONDiabetes mellitus (DM) is one of the major public health problems whose prevalence is rapidly rising all over the globe at an alarming rate. Nowhere is the diabetic epidemic more pronounced than in India, as the WHO reports show that 69.2 million people had diabetes in the year 2015.1 Patients with DM are prone to multifarious complications such as diabetic foot ulcer (DFU). DFU is a common complication of DM that has shown an growing trend over previous periods. [2][3][4] At some time in their lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
5
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 12 publications
7
5
2
Order By: Relevance
“…All of them were males between 34 to 74 years with the mean age of 56.32 years. Our findings were in concordance with studies carried out by Patil SV et al, [19] Ramani et al [20] and Viswanathan et al [21] who also reported that DFU was most common among males and late 50's age group. Male predominance may be due to the factors that males spend more time in outdoor works and exposure to traumas may be higher in these groups.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…All of them were males between 34 to 74 years with the mean age of 56.32 years. Our findings were in concordance with studies carried out by Patil SV et al, [19] Ramani et al [20] and Viswanathan et al [21] who also reported that DFU was most common among males and late 50's age group. Male predominance may be due to the factors that males spend more time in outdoor works and exposure to traumas may be higher in these groups.…”
Section: Discussionsupporting
confidence: 93%
“…Our study findings were similar to the findings of Viswanathan et al [21] and Patil SV et al [19] who also reported that mean diabetic duration was 9 years. Our study results depict that occurrence of DFU starts even with diabetic duration of 1 year.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study it showed a great sensitivity to Piperacillin-tazobactam and Imipenem similar to other studies (38,39,40 showed Proteus spp were most sensitive to Cefotaxime followed by Ceftriaxone (35,43,44). The present study showed that 100% isolates of Proteus species were sensitive to beta lactum -lactamase inhibitor combinations such as both cefoperazone-sulbactam.…”
Section: Staphylococcus Aureus (N=3)supporting
confidence: 90%
“…The understanding of bacteria associated with diabetic foot infections (DFI) and their antibiotic susceptibility profiles is essential for appropriate treatment and infection eradication. The empirical initiation of antibiotic therapy in patients with serious infections is necessary to prevent systemic invasion by infecting bacteria while awaiting microbiology laboratory results [31]. Clinicians should consider the results of bacterial culture and susceptibility testing in the light of the clinical outcome of the infection for the empirical therapy regimen.…”
Section: Microbiological Analysismentioning
confidence: 99%